Students’ perspectives regarding the institutional English courses in Universidad Surcolombiana (2023)
This narrative research study allows us to learn about the usefulness of the mandatory institutional English courses at the Universidad Surcolombiana, Neiva branch, for students of other undergraduate programs in English and their academic, professional, and personal impact. It uses the open interview anonymously to collect their experiences and to promote free expression by using questions related to the courses and based on their environment and previous contact with English using Spanish to better understand. Likewise, the English for Specific Purposes model was taken into account and presented as an idea to the students as a strategy to implement it in the different programs. The results indicated that the benefits obtained in these courses were very limited for English learning and improving the level of students, evidencing the need for English according to their program for the adequate professional development of each one.